Eco-sufistic lifestyle: gen z’s efforts in transforming environmental awareness from text to action - Nikmah, Faridatun; Anggarini, Ida Fitri; Solikhah, Khavidhotus; Ausilia, Syaila (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3586, 2025)
This study analyzes the implementation of the Eco-Sufistic Lifestyle as a manifestation of eco-theological transformation—shifting from textual understanding to concrete action—among Generation Z within Islamic educational settings, namely pondok pesantren and madrasah . Employing a descriptive qualitative approach supported by quantitative data, information was collected through in-depth interviews, observations, and questionnaires conducted in two research sites in Malang Regency. The findings reveal that the ecological awareness of students and santri ranges from high to very high, characterized by the internalization of core Sufi values such as zuhd (ascetic simplicity), anti-isrāf (anti-wastefulness), Green Mukmin, and Cosmic Tawhid. These principles foster the understanding that environmental preservation is not merely a moral duty but an integral form of worship and a spiritual responsibility of humans as khalifah (stewards) on earth. Cross-site analysis indicates that pondok pesantren emphasize exemplary conduct and discipline, while madrasah focus more on ecological education and the habituation of environmentally friendly behaviors. Despite challenges in maintaining consistency in daily practices, the integration of theological and ecological dimensions has proven effective in cultivating spiritual-ecological consciousness among learners. Therefore, the Eco-Sufistic Lifestyle emerges as a relevant Islamic educational model capable of nurturing a generation that is faithful, ethical, and environmentally conscious.